REDUCING THE BAND-GAP ENERGY OF TiO2 AS A CRUCIAL OBJECTIVE IN GREEN PHOTOCATALYSIS - Perica Paunović, Anita Grozdanov, Petre Makreski, Martin Stojčevski, Kiril Stoimčev, Gorazd Čepiševski (Ss Cyril and Methodius University in Skopje, Faculty of Technology and Metallurgy, 2025)
Green photocatalysis focuses on developing processes to address various environmental challenges, such as the treatment of contaminated water and air, the generation of renewable energy, biomass management, carbon monoxide oxidation, and organic synthesis. TiO2 nanoparticles are relatively inexpensive, non-toxic, and chemically stable. They are available in diverse structural forms and exhibit unique semiconductive properties, making them the most widely utilized photocatalysts in this domain. TiO2 has a wide array of applications in green photocatalysis, including i) photocatalytic remediation and ii) the development of alternative, sustainable energy sources. A significant challenge in modern green photocatalysis is the reduction of the band gap energy (Eg), which is essential for determining the suitability of materials for photocatalytic activity. Decreasing Eg enables TiO2 to effectively harness visible light rather than being limited to ultraviolet light. This study investigates the structural changes and subsequent reduction in Eg resulting from two types of TiO2 modification: i) ionizing irradiation and ii) the incorporation of carbon nanotubes. We synthesized TiO2 nanoparticles using our proprietary sol-gel method, followed by thermal treatment at 400 °C. Structural changes were analyzed using X-ray powder diffraction (XRPD) and Raman spectroscopy, while the band gap energy of the samples was assessed through UV-Vis spectroscopy.
Keywords: Green photocatalysis, TiO2 nanoparticles, band-gap energy, ionizing irradiation, TiO2/CNTs nanocomposites.